(untitled) (Sociologisk Forskning, 2016)
Enacting tonsillitis: Relational performances in medical practices In this paper the diagnostic process of bacterial tonsillitis at two Swedish health centres is described and analysed as to how this disease comes into being, or how it is enacted. The concept of enactment implies that disease is constituted in, and through, relational practises involving human and non-human elements. The study is based on interviews with nurses and doctors as well as field observations from the health centres. In the analysis it becomes apparent that different – and sometimes conflicting – enactments of tonsillitis appear in medical practices, depending on the organization of relations between different elements. It is concluded that diagnostic agency is created in relations between both humans and non-humans, and who and what is given diagnostic agency is changeable depending on the relations at hand. The diagnostic process of tonsillitis shows how the most mundane medical diagnoses involves a number of complex relations, that stretches beyond categories such as social and medical.